FACTORS THAT INFLUENCE READINESS FOR IMPLEMENTING STANDARD INPATIENT CLASSES AT GRANDMED LUBUK PAKAM HOSPITAL IN 2023 - Sitepu, Abdi Lestari; Kasim, Felix; Gurusinga, Rahmad (JURNAL KESMAS DAN GIZI (JKG), 2023)
Health services are a benchmark in determining the expected quality of health services in hospitals. In providing services, patients must receive the best service from the hospital to improve public health. This type of research is quantitative research using an analytical survey method with a cross-sectional approach. The population and sample in this study were all 112 inpatient rooms at Granmed Lubuk Pakam Hospital. The influencing variables are building components, air ventilation, and bed equipment. This research uses primary data in the form of observation sheets and checklists. Meanwhile, secondary data was obtained directly from the Grandmed Lubuk Pakam Hospital office. Analysis of the data used univariate and bivariate analysis. The highest Inpatient Class Building Component is in the very good category, namely 58 rooms (51.8%). The highest Inpatient Class air ventilation factor was in the very Good category with 47 rooms (42.0%). The highest Inpatient Class Bed Completeness Factor was in the Very Good category with 60 rooms (53.6%). Each factor's p-value obtained is 0.001; 0.004; 0.002 means that there is an influence of building components, air ventilation, and bed equipment on the readiness to implement standard inpatient classes at Grandmed Lubuk Pakam Hospital in 2023.